2022
DOI: 10.1038/s41598-022-12975-y
|View full text |Cite
|
Sign up to set email alerts
|

Agreements between mean arterial pressure from radial and femoral artery measurements in refractory shock patients

Abstract: Radial and femoral artery catheterization is the most common procedure for monitoring patients with shock. However, a disagreement in mean arterial pressure (MAP) between the two sites has been reported. Hence, the aim of this study was to compare the MAP from the radial artery (MAPradial) with that of the femoral artery (MAPfemoral) in patients with refractory shock. A prospective study was conducted in the medical intensive care unit. The radial and femoral were simultaneously measured MAP in the patients ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A prospective study in 2022 that included 32 patients with refractory shock found that the MAP in the radial artery was 7.6 mmHg lower than in the femoral artery. [15] Similarly, in a prospective study of critically ill patients with sepsis, the MAP of the radial artery was lower than that of the femoral artery (66±2.2 mmHg vs. 81±2.5 mmHg) when high-dose norepinephrine was used. [16] Therefore, when administering large doses of vasoactive agents, central arteries (such as the femoral artery) can be used for invasive blood pressure monitoring.…”
Section: Monitoring Methods and Medications For Blood Pressure In Cri...mentioning
confidence: 94%
“…A prospective study in 2022 that included 32 patients with refractory shock found that the MAP in the radial artery was 7.6 mmHg lower than in the femoral artery. [15] Similarly, in a prospective study of critically ill patients with sepsis, the MAP of the radial artery was lower than that of the femoral artery (66±2.2 mmHg vs. 81±2.5 mmHg) when high-dose norepinephrine was used. [16] Therefore, when administering large doses of vasoactive agents, central arteries (such as the femoral artery) can be used for invasive blood pressure monitoring.…”
Section: Monitoring Methods and Medications For Blood Pressure In Cri...mentioning
confidence: 94%
“…These trends align with typical clinical expectations as they are scenarios believed to compromise the accuracy of cuff BP measurements. 14,23 The radial artery and catheter are narrower in diameter than their femoral counterparts which may in part explain more divergent measurements; however, it is worth nothing the majority of measurements were made with radial catheters. Importantly, while these variables are statistically significant predictors in a regression model, the adjusted odds ratios are low indicating only modest ability of these factors to predict measurement disagreement.…”
Section: Discussionmentioning
confidence: 99%
“…The basic features of the included studies are summarized in Table 1; and Supplemental Table 2 (http:// links.lww.com/CCX/B343). The earliest article was published in 1987 (29), and the latest article was published in 2022 (6)(7)(8). Twenty-three studies compared the femoral artery with the radial artery, whereas one study compared the femoral artery with the brachial artery.…”
Section: Basic Features Of Included Studiesmentioning
confidence: 99%
“…Earlier studies have shown variable results regarding the concordance of blood pressure readings from different arterial sites in high-risk surgical and critically ill patients. Some studies found a good correlation between these measurements, while others observed genuine differences in systolic blood pressure (SBP) and mean arterial pressure (MAP) between central and peripheral sites (6–29). This disparity has the potential to influence clinical decision-making and patient outcomes as the accuracy of invasive blood pressure monitoring is crucial in determining the stability of the circulatory system, perfusion to major organs and hence guide the need for interventions.…”
mentioning
confidence: 99%